The inorganic body in the early Marx: a limit-concept of anthropocentrism (Práxis Educativa, 2021)
In this text, based on an interlocution with Bruno Latour’s objection to the task of criticism, Judith Butler seeks to outline a way of approaching, from a contemporary perspective, Karl Marx’s 1844 economic-philosophical manuscripts. To this end, the author interrogates a famous but enigmatic paragraph in Marx’s early writings when he refers to nature as the inorganic body of man. So, first of all, Butler finds this paragraph in the larger text of Marx and offers an understanding of this idea within the context of the author’s general arguments. Finally, she suggests that a consideration of this notion of the inorganic body in Marx has current implications for criticism, especially with regard to the charge of anthropocentrism.Keywords: Critical Theory. Body. Inorganic Nature.